2017
DOI: 10.1016/j.bbmt.2016.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DPB1 Permissive Unrelated Donors Is Highly Likely

Abstract: HLA-DPB1 permissive matching based on T cell epitope (TCE) groups should be considered when selecting among equally matched HLA-A, -B, -C, -DRB1 unrelated hematopoietic stem cell donors to improve patient survival. Previous studies have defined 3 TCE groups based on functional assays of alloreactivity. Combinations of donor and recipient DPB1 alleles with low immunogenic potential identify permissive donors, who provide no increased risk of mortality compared with DPB1-matched donors. To determine the likeliho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…This is consistent with baseline likelihoods of finding HLA-DPB1 matches with productive 10/10 searches. 61 We found that HLA-DPB1 allele mismatching did not associate with acute GVHD (P , .92), whereas TCE mismatching did associate as expected (P , .038; 1-sided Fisher's exact test), leaving 56 out of 102 acute GVHD cases (55%) unaccounted for by mismatching at 6 HLA loci.…”
Section: Donor-recipient Matching Extends Beyond Five Hla Locisupporting
confidence: 53%
“…This is consistent with baseline likelihoods of finding HLA-DPB1 matches with productive 10/10 searches. 61 We found that HLA-DPB1 allele mismatching did not associate with acute GVHD (P , .92), whereas TCE mismatching did associate as expected (P , .038; 1-sided Fisher's exact test), leaving 56 out of 102 acute GVHD cases (55%) unaccounted for by mismatching at 6 HLA loci.…”
Section: Donor-recipient Matching Extends Beyond Five Hla Locisupporting
confidence: 53%
“…The National Marrow Donor Program also provides a Web-based application that incorporates the HLA-DPB1 TCE algorithm for transplant centers to search unrelated donors and cord blood units. 31 Although HLA-DPB1 non-PM was associated with an increased risk of grade 3-4 acute GVHD, it did not affect overall survival after UR-BMT in the current JMDP analysis. We speculate that the discrepancy in transplant outcomes associated with HLA-DPB1 TCE mismatching between Caucasian and Japanese patients might be partly attributed to ethnic backgrounds.…”
Section: Discussionmentioning
confidence: 50%
“…While allele matching at DPB1 is less frequent, identifying TCE permissive donors can be highly successful. 71 Direction of the mismatch If either the recipient or donor expresses only a single HLA allele at a locus (ie, is homozygous), then a unidirectional mismatch will occur. There are 2 types of unidirectional mismatches in HCT.…”
Section: Hla Matching Considerationsmentioning
confidence: 99%